Eskimo child with wooden tub and washboard, ca. 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Mickanininie's Laundry, Alaska. Copyright 1905 by F.H. Nowell, Nome. 4238 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number